Inflammatory Myofibroblastic Tumor Masquerading as Congenital Pelvic-ureteric Junction Obstruction - Pallav Kumar; Mohammed Moinuddin Zameer; Vinay Chandrashekar; Sanjay Rao (Wolters Kluwer Medknow Publications, 2024)
Inflammatory myofibroblastic tumor (IMT) is a very rare tumor with still rare occurrence in the genitourinary system, presenting as a pelvic-ureteric junction (PUJ) obstruction (PUJO). We report a case of IMT at the PUJ mimicking congenital PUJO and review the relevant literature.